The Presentation Form, Function, and Meaning of the Ma’badong Tomakaka Music Lyrics in the Rambu Solo Ceremony of the Toraja Tribe - Brigita, Clara (Universitas Negeri Surabaya, 2025)
This research aims to describe the form of presentation, function, and meaning of Ma'badong Tomakaka music verses in the Rambu Solo traditional ceremony of the Toraja tribe. This research uses a descriptive qualitative method with an ethnomusicology approach. Data collection techniques include direct observation, interviews with sources, documentation, and literature study. Data analysis was done through data reduction, presentation, and conclusion drawing. The results showed that Ma'badong music is a traditional vocal art performed without musical instrument accompaniment in melting at formation. The singers are called Pa'badong. Ma'badong performances are held in open areas such as fields or courtyards during the day and night. A red and black shirt or t-shirt top using a Toraja woven sarong is the costume often used for Ma'badong performances. The gradual procession starts from Ma'tabe, Issi, to Ma'passundun. This music serves as a medium of ritual, entertainment, cultural identity, means of communication, and aesthetic expression in Toraja society. The poetry of Ma'badong or Kadong Badong contains deep meanings, such as moral messages, expressions of grief, prayers for the spirits to the afterlife, and hopes for the families left behind.